Influence of bile acids on the cytotoxicity of chemicals in cultivated human hepatocytes. (June 2022) - Brecklinghaus, Tim; Albrecht, Wiebke; Kappenberg, Franziska; Duda, Julia; Zhang, Mian; Gardner, Iain; Marchan, Rosemarie; Ghallab, Ahmed; Demirci Turgunbayer, Özlem; Rahnenführer, Jörg; Hengstler, Jan G.
Abstract: Bile acids (BA) are known to influence the susceptibility of hepatocytes to chemicals. We investigated the cytotoxicity of 18 compounds with known hepatotoxicity status and pharmacokinetics in cultivated primary human hepatocytes with and without the addition of a BA mix to the cell culture medium. This BA mix consisted of physiological ratios of the most abundant human BA at a cholestatic sum concentration of 0.5 mM, which corresponds to 50% of the EC10 (cytotoxicity) of the mix. The BA mix decreased the EC10 of 7 compounds by a factor greater than 1.5, but also increased the EC10 of 5 compounds. The compounds with increased susceptibility include the known hepatotoxicants and BSEP/MRP2 inhibitors rifampicin, ketoconazole, atorvastatin, and cyclosporin A. However, the cytotoxicity of some non-hepatotoxic compounds was also enhanced, among them glucose, which is not known to be an inhibitor of canalicular bile acid export. A recently established technique to quantify how well hepatotoxic and non-hepatotoxic compounds are separated by an in vitro test indicated that the addition of the BA mix did not improve separation. In conclusion, the addition of BA to cultivated hepatocytes leads to a complex situation with increased and decreased susceptibilities depending on the specific compound. Highlights: Addition of a bile acid mix to the culture medium influences the susceptibility of human hepatocytes to chemicals. Increase in susceptibility were obtained for rifampicin, ketoconazole and glucose. Increases in resistance occurred for ethanol, melatonin and acetaminophen.